Pengaruh Pendapatan per Kapita, Suku Bunga Bi Rate, Inflasi dan Kurs Dollar Amerika Serikat terhadap Simpanan Pihak Ketiga pada Bank Umum di Provinsi Bali - I Gusti Ayu Athina Wulandari; A.A. Gde Agung Parameswara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2019)
This research aims is to analyse the effect of macroeconomic variables in 4 sector economic to third party fund. Times series data period 2001-2010 has been used in this research. That period has choosen because that years Bali Blast happened until the recovery years so that we know how big are people interest to save their money in bank during that years which full of safety issues. With multiple regression analysis we have the result that only income per capita has a positive and significant effect to thirf party fund. BI interest rate, inflation, and US dollar exchange has no significant effect to third party fund.